Pan-cancer and single-cell analyses identify CD44 as an immunotherapy response predictor and regulating macrophage polarization and tumor progression in colorectal cancer - Zhang, Qian; Wang, Xinyu; Liu, Yang; Xu, Hao; Ye, Chun (Frontiers in Oncology, 2024)
Cluster of differentiation (CD) 44 is a non-kinase cell surface transmembrane glycoprotein involved in a diversity of biological processes. The expression of CD44 elevated in most cancers, predicting poor prognosis. The cBioportal database was utilized to describe the genomic alteration profile of CD44.The CancerSEA database was used to analyze the involvement of CD44 in various biological processes participated in cancer progression.The immune characteristics of CD44 were comprehensively explored by TIMER2.0 and CIBERSORT. Further, we found CD44 was highly expressed in in myeloid lineage at a single-cell level. Pseudotime trajectory analysis of CD44 gene expression was performed using Monocle2, and CellChat was utilized to compare the crosstalk differences between CD44+ monocytes and CD44- monocytes. Tumor immune dysfunction and exclusion (TIDE) analysis revealed that CD44 had good predictive ability for immune checkpoint blockade (ICB) responses.Knockdown of CD44 inhibited the proliferation, migration, and invasion of colorectal cancer (CRC) cells in vitro. In addition, knockdown of CD44 in macrophages inhibited M2 macrophage polarization. Inhibiting the expression of CD44 in M2 macrophages alleviated the M2 macrophage-induced migration effect on HCT-116 cells. These findings suggested that CD44 is involved in regulating tumor development, macrophage polarization transformation, and has certain predictive value for patient clinical prognosis and response to immunotherapy.